“Tell Someone,” to Both Women and Men - Duque, Elena; Melgar, Patricia; Gómez-Cuevas, Sara; López de Aguileta, Garazi (Frontiers in Psychology, 2021)
Contrary to an understanding of the struggle against gender violence as placing men and women in opposition to one another, victims have always been supported by both women and men. To prevent violence is important to know not only which message should be transmitted but also how the dialogue should unfold, and the characteristics of the people engaging in that dialogue. Because of the existing association between attraction and violence in our society, the unity of the language of ethics and the language of desire in such dialogue has become a key element in the struggle against gender violence. This study identifies the strong presence of communicative acts that unify these languages in the women (feminism) and men (New Alternative Masculinities) who are successful in this struggle. The opposition to violence that they defend guide their own desires, which are transmitted through their communicative acts to the people around them.